Cardioprotective effects of Aconiti Lateralis Radix Praeparata combined with Zingiberis Rhizoma on doxorubicin-induced chronic heart failure in rats and potential mechanisms. (28th June 2019) - Wen, Jianxia; Zou, Wenjun; Wang, Ruilin; Liu, Honghong; Yang, Yuxue; Li, Haotian; Wei, Shizhang; Li, Ruisheng; Cai, Huadan; Wang, Jian; Zhao, Yanling
Abstract: Background: The combined use of Aconiti Lateralis Radix Praeparata (ALRP) and Zingiberis Rhizoma (ZR) are classic compatibilities in China for the treatment of cardiovascular diseases such as increasing myocardial contractility, anti-arrhythmia, reducing myocardial oxygen consumption, and dilating organ blood vessels, etc, thereby exerting anti-heart failure (HF) effects in traditional Chinese herbal medicine. However, comprehensive approaches for understanding the therapeutic effects and mechanisms underlying chronic heart failure (CHF) from the perspective of energy metabolism have not been pursued. Aim: This research was aimed to investigate the effectiveness and potential mechanism of ALRP combined with ZR (1:1) on doxorubicin (DOX)-induced CHF in rats based on an integrated approach that combines network pharmacology analyses and molecular biology. Material and methods: CHF model was established by the intraperitoneal injection of DOX. ALRP and ZR were intragastrically administrated for three weeks. The detection indices including hemodynamic measurements, myocardial injury marker, and myocardial pathological changes were measured. Network pharmacology analysis was used to illustrate the pathways and network of ALRP and ZR against HF. Mitochondrial energy metabolism pathway associated gene and protein levels of PPARα, PGC-1α and Sirt3 in myocardial tissue were detected by real-time PCR and western blotting, respectively. Results: The results indicated that ALRP-ZR herbal couple significantly improved the left ventricular function and cardiac enzyme activities in comparison with their single use. Network pharmacology analysis results showed that the pharmacological mechanisms of ALRP-ZR may be related to PPAR energy metabolism pathway. Besides, the outcomes of western-blot and real-time PCR analysis showed that ALRP-ZR significantly upregulates the protein and gene level of PPARα, PGC-1α, and Sirt3. Conclusions: Network pharmacology analysis would be an effective network analyze workflow which was feasible for evaluating the pharmacological effect of a multi-drug complex system. The Chinese herbal couple ALRP-ZR had a better therapeutic effect than their single-use against DOX-induced CHF, which may be related to enhancing left ventricular function by activating the PPARα/PGC-1α/Sirt3 pathway. Graphical abstract: Image 1